Analysis of Learner Types According to Self-Efficacy and Team-Member Exchange: Using K-means Clustering - Mi-Jin Ra; Min-Jung Jin (Hanggong uju uihakoeji)
Purpose: This study investigates the relationship between self-efficacy and teammember exchange (TMX) among aviation service students, and examines how these factors influence academic achievement and collaborative behavior. Self-efficacy, based on Bandura’s Social Cognitive Theory, is defined as an individual’s belief in their ability to overcome challenges, while TMX reflects the quality of social exchanges among team members. Methods: A convenience sample of undergraduate students from an aviation service department was recruited, yielding 65 valid responses. Self-efficacy was measured using the New General Self-Efficacy Scale along with additional validated items, and TMX was assessed with a TMX-10 scale, both utilizing a 5-point Likert scale. Data analysis included descriptive statistics, K-means clustering to identify behavioral segments, ANOVA for group comparisons, and regression analysis to explore the relationship between self-efficacy and TMX. Results: The analysis revealed four distinct behavioral clusters: confident collaborator, team player, reserved individual, and solo achiever. Results indicated that higher selfefficacy is associated with enhanced TMX and academic performance. Moreover, significant differences in self-efficacy and TMX scores were observed across the clusters, and regression analysis confirmed a positive relationship between selfefficacy and the quality of team interactions. Conclusion: These findings highlight the importance of fostering both self-efficacy and effective team exchanges to optimize collaborative learning environments in aviation service education. Tailored educational interventions based on behavioral clustering can further enhance academic outcomes and prepare students for professional challenges.